2013
DOI: 10.2337/db12-1219
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Assessing Mitochondrial Function in Diabetes

Abstract: A growing body of research is investigating the potential contribution of mitochondrial function to the etiology of type 2 diabetes. Numerous in vitro, in situ, and in vivo methodologies are available to examine various aspects of mitochondrial function, each requiring an understanding of their principles, advantages, and limitations. This review provides investigators with a critical overview of the strengths, limitations and critical experimental parameters to consider when selecting and conducting studies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
141
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(142 citation statements)
references
References 167 publications
(215 reference statements)
0
141
0
1
Order By: Relevance
“…Some studies have done this (Brand et al, 1991;Hulbert et al, 2002a;Pamplona et al, 1999aPamplona et al, , 1999cPamplona et al, , 1996, but the methods used in these studies have their own problems, including a lack of reliability in measures of lipid peroxidation used and disruption of mitochondrial structure in isolated mitochondria (Halliwell and Whiteman, 2004;Perry et al, 2013;Zhang et al, 2012).…”
Section: Using One Organ To Estimate Whole Organism Effectsmentioning
confidence: 99%
“…Some studies have done this (Brand et al, 1991;Hulbert et al, 2002a;Pamplona et al, 1999aPamplona et al, , 1999cPamplona et al, , 1996, but the methods used in these studies have their own problems, including a lack of reliability in measures of lipid peroxidation used and disruption of mitochondrial structure in isolated mitochondria (Halliwell and Whiteman, 2004;Perry et al, 2013;Zhang et al, 2012).…”
Section: Using One Organ To Estimate Whole Organism Effectsmentioning
confidence: 99%
“…1). Further, where it has been previously hypothesized that 60 mmol·L −1 lactobionate used in the respiration buffer may inhibit LDH (Passarella et al 2014), we replaced our buffer with the frequently employed buffer Z (Perry et al 2013) and observed no increase in respiration ( Supplementary Fig. S1 1 ), demonstrating that lactobionate does not have an inhibitory effect on lactate metabolism.…”
Section: Lactate Oxidation In Permeabilized Mouse Brainmentioning
confidence: 99%
“…The method was developed to ensure H 2 O 2 could be determined, and therefore taurine was removed from the buffer, as originally reported (Herbst and Holloway 2015); taurine was excluded in the current study to be consistent with those experiments. MiR05 media was chosen following preliminary experiments comparing it to another popular, but notably sucrose-and lactobionate-free potassium salt buffer (buffer Z (Perry et al 2013)), owing to differences in maximal respiration ( Supplementary Fig. S1 1 ).…”
Section: Respirometrymentioning
confidence: 99%
“…Permeabilization of insulinoma cell lines has been performed with saponin (89,91,96,98,139,269), staphylococcal ␣-toxin (246,323,324,326), streptolysin-O (117), or perfringolysin-O (260) or by electropermeabilization (459). The advantages and limitations inherent in these permeabilization strategies have been recently reviewed, with a focus on mitochondrial function in skeletal muscle (408).…”
Section: Permeabilized Cell Preparationsmentioning
confidence: 99%